2008
DOI: 10.1111/j.1865-1682.2007.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Concentrations in Products of Animal Origin

Abstract: Foot-and-mouth disease (FMD) is a highly contagious disease of cloven-hoofed animals which can have devastating economic consequences. Maintaining an FMD-free status is a priority for non-endemic countries, which restrict importation of animals and animal products from countries in which the disease is present or sporadic, thus presenting a considerable barrier to international trade. This review examines the concentration of FMD virus in animal tissues during the viraemic stage of disease and in animal produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Moreover, the spread of the disease is facilitated by the ability of the virus to survive for relatively long periods in raw meat, raw milk or outside the host [1,10,11]. Infection of cloven-hoofed animals can result in development of a carrier state in which case FMDV may be found in such animals for more than 28 days after infection [12-14], and thus may influence the epidemiology of the disease and interfere with its diagnosis and control.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the spread of the disease is facilitated by the ability of the virus to survive for relatively long periods in raw meat, raw milk or outside the host [1,10,11]. Infection of cloven-hoofed animals can result in development of a carrier state in which case FMDV may be found in such animals for more than 28 days after infection [12-14], and thus may influence the epidemiology of the disease and interfere with its diagnosis and control.…”
Section: Introductionmentioning
confidence: 99%
“…During the viraemic phase, a blood 14 titre of 10 5.6 PFUs/mL was reported by Cottral (1969) for cattle, while a blood titre of 10 7.2 ID 50 /g was reported by Sellers (1971) for pigs and a blood titre of 10 5.0 PFUs/mL by Burrows (1968) for sheep. From the data compiled by Ryan et al (2008), it can be concluded that infective virus can still be found in animal tissues and products where high starting titres can be assumed after several months at low temperatures (below 0 ºC or 4 ºC) and after 1 month at ambient temperatures, e.g. the small and large intestines used for the production of casings), is probably dependent on the blood titres during viraemia.…”
Section: Foot and Mouth Disease Virusmentioning
confidence: 99%
“…Routes may be illegal live‐aquatic animal movements, movements of aquatic animals incubating the disease or reared under environmental conditions where the disease was not apparent, non‐live aquatic animal movements or poor implementation of import trade measures. Such trade of animal products is a recognized risk for the spread of terrestrial animal diseases, for example foot‐and‐mouth disease and classical swine fever (Williams and Matthews, 1988; MacDiarmid and Thompson, 1997; Anderson, 2002; Pharo, 2002; Ryan et al., 2008). Uncontrolled commodity trade is also recognized as a possible route for spread of aquatic animals pathogens: pilchard herpesvirus is thought to have been introduced to Australia through the import of frozen pilchards for tuna feed (Gaughan, 2002); the myxosporidian parasite Myxobolus cerebralis is believed to have been introduced into North America with frozen fish (Elson, 1969; Hoffman, 1970); and WSSV is likely to have reached the USA in frozen shrimp (Lightner et al., 1997).…”
Section: Introductionmentioning
confidence: 99%